Family - Kingsbury, Karen (Kingsbury, Karen. Firstborn series, 2011)
After finding his firstborn son, John Baxter looks for a way to tell his other children, while a sensational Hollywood trial reunites Dayne Matthews and Katy Hart, but just when love has the chance to win, doubts and presumed scandals push them further apart.